PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KOMPETENSI PROFESIONAL GURU PADA SEKOLAH DASAR - Pareang, Darmady; Malik, Marwati Abdul; Warsihna, Jaka (Kelola: Journal of Islamic Education Management, 2023)
As a profession, teacher fields are not separated from competence matter, so that the teacher does not only have to have enough knowledge, but they are required to increase the professional competency. The study aimed to examine dan analyse the influence of education and training on teacher’s professional competency. The study was conducted by survey method with written questionnaire toward teachers at elementary school in the Dictrict of North Makale Tana Toraja Regency. The number of samples in this research were seventy nine respondents by purposive sampling method with a criteria which has teaching experience at least one year. The examined of hypothesis was using Linier Regression Analysis by Statistical Package for the Social Sciences (SPSS) version 23. The results of research indicate that education and training positively and significantly influence on teacher’s professional competency, as partial or simultaneous. Determine coefficient R Square value of 0.717 indicates that the variation in teacher’s professional competency at elementary school in the Dictrict of North Makale Tana Toraja Regency determine by education and training within 71.7 percent, while theremaining 28.3 percent determine by other factors out of the independent variables in this research. The research indicates that the teacher’s professional competency has the relationship with the level of education and training of teacher.